REM: Automatic for the People - Emilio Molinari; Stefano Covino; Francesco D'Alessio; Dino Fugazza; Giuseppe Malaspina; Luciano Nicastro; Mauro Stefanon; Vincenzo Testa; Gino Tosti; Fabrizio Vitali (Advances in Astronomy)
We present the result of a year-long effort to think, design, build, realize, and manage the robotic, autonomous REM observatory, placed since June 2003 on the cerro La Silla, ESO Chile. The various aspects of the management and control are here surveyed, with the nice ideas and the wrong dead ends we encountered under way. Now REM is offered to the international astronomical community, a real, schedulable telescope, automatic for the People.